The Antecedents of Muslim Tourists' Revisit Intention: The Mediating Role of Visitor Satisfaction - Faisol Habibi; Indri Supriani; Yunice Karina Tumewang (Shirkah: Journal of Economics and Business, 2025)
This study aims to investigate the key antecedents influencing the revisit intentions of Muslim tourists to Batu City, East Java, Indonesia. Specifically, the research examines the impact of destination image, service quality, availability of halal facilities, and visitor income on the propensity to revisit, with visitor satisfaction introduced as an intervening variable. Utilizing 209 samples, the data is analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS) to assess the direct and indirect relationships between the variables. The results demonstrate that destination image exerts a significant and positive effect on Muslim tourists' intention to revisit Batu City, while service quality, halal facilities, and visitor income show no statistically significant direct impact. However, all four factors—destination image, service quality, halal facilities, and visitor income collectively enhance visitor satisfaction, which in turn mediates their indirect influence on revisit intentions. This research offers valuable insights for local governments, tourism stakeholders, and academic circles by identifying factors crucial for improving the Muslim visitor experience. The findings have practical implications for enhancing the attractiveness of Batu City as a tourism destination, ultimately contributing to increased visitation rates among Muslim tourists.